Coupled nonlinear oscillation and stability evolution of viscoelastic dielectric elastomers. Issue 38 (14th October 2015) - Zhang, Junshi; Chen, Hualing; Li, Bo; McCoul, David; Pei, Qibing
<x xml:space="preserve">Abstract</x> This article describes the development of an analytical model to study the coupled nonlinear oscillation and stability evolution of viscoelastic dielectric elastomers under non-equibiaxial tensile forces.